2017
DOI: 10.1021/acsami.7b01532
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Reduction of High Valence Ni States in Mesoporous NiO Film for Solar Cell Application

Abstract: The most common material for dye-sensitized photocathodes is mesoporous NiO. We transformed the usual brownish NiO to be more transparent by reducing high valence Ni impurities. Two pretreatment methods have been used: chemical reduction by NaBH and thermal reduction by heating. The power conversion efficiency of the cell was increased by 33% through chemical treatment, and an increase in open-circuit voltage from 105 to 225 mV was obtained upon heat treatment. By optical spectroelectrochemistry, we could iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 35 publications
3
71
0
Order By: Relevance
“…It has been confirmed that, as shown in Figure S4A in the Supporting Information, the solar cells with NiO x sputtered using a low oxygen partial pressure have a higher performance than those of the devices with NiO x sputtered using a high oxygen partial pressure. A possible reason is that the presence of excess Ni 3+ in the film sputtered from a high oxygen partial pressure may be responsible for the high rate of recombination, which has also been widely reported in the dye‐sensitized solar cells previously 42, 43, 44. However, further explanation of this improvement is needed, which is out of the scope of this paper.…”
mentioning
confidence: 89%
“…It has been confirmed that, as shown in Figure S4A in the Supporting Information, the solar cells with NiO x sputtered using a low oxygen partial pressure have a higher performance than those of the devices with NiO x sputtered using a high oxygen partial pressure. A possible reason is that the presence of excess Ni 3+ in the film sputtered from a high oxygen partial pressure may be responsible for the high rate of recombination, which has also been widely reported in the dye‐sensitized solar cells previously 42, 43, 44. However, further explanation of this improvement is needed, which is out of the scope of this paper.…”
mentioning
confidence: 89%
“…where the holes h + (NiO) localized on the NiO surface represent the defective Ni(III) sites of the pristine oxide [23,26]. This is equivalent to say that chemisorbed ERY induces the chemical conversion Ni(III) → Ni(II).…”
Section: Dyementioning
confidence: 99%
“…Moreover, FG introduces an additional peak of oxidation due to the electroactivity of the dye itself (see the comparison of the two traces in the left frame of Figure 3). where the holes h + (NiO) localized on the NiO surface represent the defective Ni(III) sites of the pristine oxide [23,26]. This is equivalent to say that chemisorbed ERY induces the chemical conversion Ni(III) → Ni(II).…”
Section: Dyementioning
confidence: 99%
See 1 more Smart Citation
“…Such properties are in turn influenced by the modality with which the dye is anchored onto the surface, the chemisorption geometry being dependent on the nature of the sensitizer and on the surface properties of the semiconductor like morphology, chemical composition,,, and charge/potential distribution at the interface ,. In addition to that, the type of electronic interactions existing between the relevant orbitals of the sensitizer in the excited stateand the electronic structure of the nanostructured semiconductorare also of primary importance for the identification of the actual mechanism of electron transfer. In fact, the latter process can occur either via electron tunnelling or via the macro‐orbital obtained from the mixing of the molecular orbital(s) of the excited dye with the electronic surface states of the supporting semiconductor ,.…”
Section: Introductionmentioning
confidence: 99%